Comparative analysis of the contribution to the United Nations Sustainable Development Goals through non-financial information disclosed by IBEX 35 companies - Esperanza Calvo-Centeno; Enrique Gragera-Pizarro; Eva Romero-Ramos; Eva Ropero-Moriones (Financial Internet Quarterly, 2022)
The purpose of this research is to examine the non-financial key performance indicators contem- plated in Directive 2014/95/EU through the prism of the Sustainable Development Goals (SDGs). To do this, the presence of the indicators contemplated in the United Nations 2030 Agenda in the non-financial information disclosed by the groups of companies listed in the Spanish IBEX 35 index in the years 2017 and 2019 has been analyzed. The obtained results show an increase in the presence of SDGs in the non-financial reports of IBEX35 listed companies. Furthermore, the statistical analysis reveals that there are no significant differences in the number of SDGs incor- porated as non-financial key performance indicators between the different business sectors. The methodology used in this research also constitutes a tool that can be used to learn about the implementation of social and environmental policies in other companies
Keywords: M48; M41; Q56; M21; 330; Directive 2014/95/EU; Sustainable Development Goals; SDGs; Thematic Content Analysis; Legitimacy Theory